2016
DOI: 10.1016/j.ccell.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A Designed Inhibitor of p53 Aggregation Rescues p53 Tumor Suppression in Ovarian Carcinomas

Abstract: SUMMARY Half of all human cancers lose p53 function by missense mutations, with an unknown fraction of these containing p53 in a self-aggregated, amyloid-like state. Here we show that a cell-penetrating peptide, ReACp53, designed to inhibit p53 amyloid formation, rescues p53 function in cancer cell lines and in organoids derived from high-grade serous ovarian carcinomas (HGSOC), an aggressive cancer characterized by ubiquitous p53 mutations. Rescued p53 behaves similarly to its wild-type counterpart in regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
363
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(390 citation statements)
references
References 59 publications
25
363
2
Order By: Relevance
“…For NM, as with many other amyloid-forming proteins such as TTR (48), Tau (49), and p53 (50), much of the detailed structural work has been focused on small peptides derived from aggregation-prone regions of a fulllength protein. The peptide GNNQQNY corresponds to residues 7 to 13 of the 253-residue-long NM.…”
Section: Discussionmentioning
confidence: 99%
“…For NM, as with many other amyloid-forming proteins such as TTR (48), Tau (49), and p53 (50), much of the detailed structural work has been focused on small peptides derived from aggregation-prone regions of a fulllength protein. The peptide GNNQQNY corresponds to residues 7 to 13 of the 253-residue-long NM.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic scanning of the p53 sequence suggested that a conserved aggregation-prone peptide (residues 251-258) within the DNA-binding domain of WT p53 might represent the nucleation site for aggregate formation (Fig. 3) (Xu et al 2011;Ghosh et al 2014;Rangel et al 2014;Soragni et al 2016). Further studies of this short segment using synthetic peptides revealed that it formed amyloid-like aggregates with WT p53 and coaggregated with p63/p73, leading to the inhibition of their functions (Xu et al 2011;Ghosh et al 2014).…”
Section: Mechanisms Underlying the Prion-like Aggregation Of Tumor Sumentioning
confidence: 99%
“…R248Q mutant p53 has been previously shown to aggregate in breast cancer biopsies and cell lines (Levy et al 2011;Ano Bom et al 2012). RecACp53 was also able to reduce in vivo xenograft growth and metastasis (Soragni et al 2016). RecACp53 had no effects when the cells had WT p53.…”
Section: New Approaches For Cancer Therapy Involving P53 Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancement in technology, structural proteomics and information from sequencing data have enabled more efficient screening and validation of tumor-associated antigens (TAAs) that may be targeted by T cells (Battaglia and Muhitch, 2016). For instance, the understanding of the structure of tumor antigen p53, in ovarian cancer, led to the design of an effective p53 peptide inhibitor (Soragni et al, 2016). Structural understanding of TAAs recognized by effector T cells and design of therapies based on the TCR-pMHC interaction could be useful in combination with ACT.…”
Section: T Cell Receptorsmentioning
confidence: 99%